ANALISIS FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MELAKUKAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN (PBB-P2): Studi Kasus Badan Pengelola Keuangan, Pendapatan dan Aset Daerah Kabupaten Tapanuli Utara - Meliati Meliati; Arthur Simanjuntak; Ivo Maelina Silitonga; Thomas Sumarsan Goh (Jurnal Ilmu Manajemen METHONOMIX, 2022)
This study aims to analyze the effect of knowledge of rural and urban land and building taxes, taxpayer awareness, rural land and building tax services, tax sanctions, and NJOP on taxpayer compliance. This type of research is survey research, using primary data with a questionnaire. The research population was 110,077 and 105 processed. Hypothesis testing was carried out using multiple linear regression using the Statistical Package for the Social Sciences (SPSS). The results showed that knowledge of rural and urban land and building taxes, taxpayer awareness, rural and urban land and building tax services, tax sanctions, and NJOP had a significant effect on taxpayer compliance. Taxpayer awareness and land and rural and urban tax services have no significant positive effect on taxpayer compliance. Partially, knowledge of rural and urban land and building taxes, taxes, taxes, and NJOP have a positive effect on taxpayer compliance. While the awareness of taxpayers and services for rural and urban land and building taxes has a positive and insignificant effect on taxpayer compliance.